Functional results and photic phenomena with new extended-depth-of-focus intraocular Lens - Bert C. Giers (BMC Ophthalmology, 2019)
Abstract Background Evaluation of clinical and functional results of a new extended depth of focus intraocular lens (EDOF-IOL). Methods Fourteen cataract patients (28 bilateral implantations) were assessed for uncorrected (UDVA) and corrected (CDVA) distance visual acuities; uncorrected (UNVA), distance-corrected (DCNVA) and best corrected (CNVA) near visual acuities; and uncorrected (UIVA) and distance-corrected (DCIVA) intermediate visual acuities - as well as binocular defocus curves. Photopic and mesopic contrast sensitivity was recorded. Reading acuity was evaluated using an electronic reading desk at fixed distances and at the patient’s preferred near and intermediate distances. Visual symptoms were assessed with a halo and glare simulator plus a patient questionnaire which also recorded quality of life. Results Median postoperative monocular UDVA was 0.13logMAR (range − 0.08 to 0.42logMAR), median CDVA was − 0.01logMAR (range − 0.20 to 0.22logMAR), median UIVA at 80 cm was − 0.05logMAR (range − 0.18 to 0.58logMAR) and median UNVA at 40 cm was 0.14logMAR (range − 0.10 to 0.64logMAR). Binocular uncorrected reading acuity was 0.10logMAR at 40 cm and 0.11logMAR at 80 cm. Patients preferred a median intermediate reading distance of 62.8 cm over the predetermined 80 cm, which allowed them to read smaller letter size but did not improve reading acuity. Patients reported a high rate of spectacle independence and satisfaction in everyday life and little to no dysphotopsia. Conclusion The Mini WELL Ready IOL provided good postoperative functional results at far and intermediate distances and improved the visual and reading acuity at reading distance. The lens caused little to no dysphotopsia. Trial registration The study protocol was registered at the German Clinical Trials Register: DRKS00007837 (Registered Date: March 9th, 2015).